Diet Pattern and Dyslipidemia Among Type II Diabetes Mellitus Patients Diagnosed More Tthan One Year Visiting Tribhuvan University Teaching Hospital (Nepalese Medical Journal, 2021)
Introduction: Dyslipidemia is a risk factor for coronary artery disease, a leading cause of mortality in patients with type 2 diabetes mellitus. This study aims to study the dietary pattern and dyslipidemia of type 2 diabetes mellitus patients visiting Tribhuvan University Teaching Hospital.Materials and Methods: Quantitative study was done to find out the dietary pattern and dyslipidemia of type 2 diabetes mellitus patients visiting Tribhuvan University Teaching Hospital. Patients with type 2 diabetes mellitus diagnosed for more than one year were included in the study.Results: The percentage of dyslipidemia in type 2 diabetes mellitus was found to be 88.5%. Dyslipidemia was found to be significantly associated (p